Home mobility hazards detected via object recognition in augmented reality - Eloy, S. (2021)
We present an Environmental Analysis and Safety Advisor system capable of identify the environmental barriers and hazards found in the homes of elderly people. This augmented reality tool runs on a portable computing device and can be used by informal and formal caregivers without specific knowledge of Accessible Design, to evaluate the safeness of an elderly home environment, ensuring that potential fall hazards are detected and corrected. The system recognizes specific indoor elements of the house (e.g. arm-chair, bed, chair), and then computes and analyses their mutual distances in the environment so that a warning of hazard is emitted in case of need (e.g. loose cable, not enough space to pass a wheelchair). In this context, we implemented object recognition at the category level of miniature versions of real sized furniture and the determination of the distance between neighboring objects, signaling if it is below a certain threshold value. Environmental Analysis tool can then recognize furniture and measure the distance between two furniture elements enabling the system to pop up an alert sign if the space left does not guarantee good accessibility.